Practice Guidelines for the Value Evaluation of Clinical Pharmacy Services (version 2) - Wu, Liuyun; Lv, Ziyan; Chen, Min; Zheng, Xingyue; Li, Lian; Du, Shan; Han, Lizhu; Yin, Qinan; Wang, Yin; Liu, Xinxia; Li, Wenyuan; Huang, Xuefei; et al. (Frontiers in Public Health, 2025)
ObjectiveTo optimize the construction of pharmaceutical services in medical institutions, advance the development of clinical pharmacy as a discipline, enhance the level of clinical pharmacy services, systematically implement and evaluate clinical pharmacy practices, and improve patient therapeutic outcomes, we have developed the Practice Guidelines for the Value Evaluation of Clinical Pharmacy Services (Version 2).MethodsThis guideline was designed following the World Health Organization (WHO) Guideline Development Manual. The Delphi method was employed to identify clinical questions. A comprehensive systematic search was conducted to collect existing evidence on relevant issues, and the systematic reviews, evidence grading, and evidence summaries were subsequently compiled. The guideline employs the Joanna Briggs Institute (JBI) evidence level system from Australia and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system introduced by WHO in 2004 to classify the quality of evidence. Consensus on the recommendations and evidence levels was achieved through the Delphi method, resulting in the formation of the Practice Guidelines for the Value Evaluation of Clinical Pharmacy Services (Version 2).ResultsThrough a questionnaire survey of over 100 experts and the Delphi method voting, 23 preliminary indicators for evaluating the value of clinical pharmacy services were identified. The content of these included indicators was searched according to the PICO principle, followed by systematic reviews, meta-analyses, network meta-analyses, and related original research. Each search strategy was reviewed and approved by the guidelines steering committee. Ultimately, three dimensions for evaluating the value of clinical pharmacy were identified, encompassing 15 indicators, resulting in 20 recommendations.ConclusionThis guideline presents a set of metrics to assess the quality and effectiveness of clinical pharmacy services, which is crucial for enhancing and elevating clinical pharmacy services in healthcare institutions.Systematic review registrationhttp://www.guidelines-registry.org/guide/28502a74-7038-439c-bdee-d355747e2a9d, identifier: PREPARE-2022CN756.